ELLMAN’S REAGENT FOR ANALYSIS OF o-CHLOROBENZYLIDENE MALONONITRILE (CS RIOT CONTROL AGENT) IN SOLID SAMPLES - Vladimír Pitschmann; Lukáš Matějovský; Zbyněk Kobliha (Journal of the Chilean Chemical Society, 2019)
We propose a new method of spectrophotometric determination of o-chlorobenzylidene malononitrile (CS riot control agent) in solid samples of various origins and compositions (soil, brickwork, silica gel, glass wool). The method is based on colouring reaction of malononitrile with Ellman’s reagent in the presence of ammonium acetate as a catalyst. The reaction proceeds in a non-aqueous medium. The analysis takes place in an aprotic solvent N,N-dimethylformamide, which is also an extraction reagent. A detection limit is 0.18 μg mL-1, calibration curve is linear in the range of 0.34 – 10.20 μg mL-1. The method is suitable for an analysis in laboratory as well as in field conditions.